The Intellectual property in the Mexico-Japan Economic Association Agreement - Fernando Alfonso Rivas Mira (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2007)
This article is about the commercial and cooperation clauses in Intellectual Property Rights contained in the Agreement of Economic Association between Mexico and Japan The author describe the clauses and interpret them in terms of its possible impact and also in terms of the national interest assumed by the Mexican Government.